Stepwise hydrolysis to improve carbon releasing efficiency from sludge. (1st August 2017) - Liu, Hongbo; Wang, Yuanyuan; Wang, Ling; Yu, Tiantian; Fu, Bo; Liu, He
Abstract: Based on thermal alkaline hydrolysis (TAH), a novel strategy of stepwise hydrolysis was developed to improve carbon releasing efficiency from waste activated sludge (WAS). By stepwise increasing hydrolysis intensity, conventional sludge hydrolysis (the control) was divided into four stages for separately recovering sludge carbon sources with different bonding strengths, namely stage 1 (60 °C, pH 6.0–8.0), stage 2 (80 °C, pH 6.0–8.0), stage 3 (80 °C, pH 10.0) and stage 4 (90 °C, pH 12.0). Results indicate stepwise hydrolysis could enhance the amount of released soluble chemical oxygen demand (SCOD) for almost 2 times, from 7200 to 14, 693 mg/L, and the released carbon presented better biodegradability, with BOD/COD of 0.47 and volatile fatty acids (VFAs) yield of 0.37 g VFAs/g SCOD via anaerobic fermentation. Moreover, stepwise hydrolysis also improved the dewaterability of hydrolyzed sludge, capillary suction time (CST) reducing from 2500 to 1600 s. Economic assessment indicates stepwise hydrolysis shows less alkali demand and lower thermal energy consumption than those of the control. Furthermore, results of this study help support the concepts of improving carbon recovery in wastewater by manipulating WAS composition and the idea of classifiably recovering the nutrients in WAS. Graphical abstract: Highlights: A strategy of stepwise hydrolysis was developed to improve carbon release efficiency from WAS. Stepwise hydrolysis simultaneously enhanced the amount and quality of released carbon from WAS. Stepwise hydrolysis improved the dewaterability of hydrolyzed WAS. Extracellular matters in WAS has much better biodegradability than intracellular matters. Concepts of improving carbon recovery and classifiably recovering nutrients were introduced.